Memperkasa kepimpinan ahli akademik Anak Generasi Felda (AGF): suatu analisis daya tahan - Azman, Norzaini; Sanusi, Zainal Abidin (UTM Press, 2014)
The purpose of the study is to examine the resiliency characteristics of FELDA first generation academics namely: engagement; challenges and control, while the academics were growing up in the FELDA environment. The study employed a qualitative methodology that included semi structured interviews involving 68 academics from seven public universities who were identified as FELDA first generation. The findings showed that persistence and hardship due to their socioeconomic disadvantages while growing up in FELDA environment had resulted the respondents to be more resilient in escaping from poverty. The FELDA first generation academics somehow managed to turn their challenges into opportunities and worked harder towards success. These findings indicate that the academics from FELDA are able to overcome various forms of adversity in their lives. The respondents also seemed to possess resiliency characteristics which are optimism, locus of control and hardiness. Besides providing implications for further understanding of resiliency characteristics among FELDA first generation academics, this study also suggests strategies for recruiting and training university young academic talents particularly in their professional advancement activities.